Prevalence of Exclusive Breastfeeding and Factors Influencing Infant Feeding Practices among Mothers of Central Nepal - Panthi, Srijana; Koirala, Pallavi; Bansal, Prerna; Prasai, Meera; Khadka, Kamal; Phyual, Ranjeeta; Shrestha, Ayasha (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Infants should be exclusively breastfeed for the first six months of life to achieve optimal growth, development and health. Considered as an ideal food for infants, it also helps to fight disease like diarrhea and pneumonia. In Nepal only two third of the mother exclusively breastfeed their child in the past 24 hrs. The aim of this study is to find prevalence of exclusive breastfeeding and factors influencing infant feeding practices among mothers. Methods A cross-sectional study was conducted in Bharatpur, Chitwan among 290 lactating mothers at the Immunization Center of Bharatpur Hospital Chitwan. Mothers were interviewed on details regarding feeding of their child. Results The mean age of the study population was 25.6 ± 4.5 years. A majority of the respondents were <30 years of age (234, 82.4%), primipara (175, 61.6%) and living in a joint family (199, 70.1%). Exclusive breast feeding (EBF) was practiced by 203 (71.5%) mothers on the current infant. Low production of milk was the commonest reason for not practicing EBF (66.6%). Over two-thirds (195, 68.7%) had started breastfeeding within 1 hour of delivery. Cesarean section was the most frequent cause (71, 88.6%) for late initiation of breastfeeding. Conclusions The study revealed that Prevalence of Exclusive Breast Feeding is 71.5% and 93.5% of respondents had heard of EBF. Low production of milk was the commonest reason for not practicing EBF (66.6%). Still 28.5% mothers did not practice EBF, 7.7 %mothers had not heard of EBF, indicating a need for EBF promotion which could be carried out within the existing healthcare system such as the antenatal and vaccination clinics.